017 Paradoxical reaction in tuberculous meningitis: a tertiary referral hospital retrospective experience of concomitant immunosuppression therapy. Issue 6 (24th May 2018) - Ledingham, David; El-Wahsh, Shadi; Cappelen-Smith, Cecilia; Hodgkinson, Suzanne; McDougall, Alan; Maley, Michael; Cordato, Dennis
Abstract : Introduction: Tuberculous meningitis (TBM) accounts for <1% of all tuberculosis (TB) presentations. Paradoxical reactions (PR) in non-HIV patients are a common manifestation of anti-tuberculosis therapy characterised by clinico-radiological deterioration. We report a case series of TBM admissions to our institution, including two cases with corticosteroid-refractory PR who responded to adjuvant cyclosporin. Methods: Retrospective review of 12 HIV-negative patients admitted to Liverpool Hospital, Sydney (2005–2017) with laboratory and/or radiologically confirmed TBM. Results: Median age 40 (range 22–81 years), 7 males. Eleven patients were of Asia-Pacific origin. All eleven presented with central nervous system manifestations and 1 had preceding miliary TB. Nine patients had extra-cranial TB involvement, including 8 with past or current pulmonary disease. Cerebrospinal fluid (CSF) TB PCR/culture was positive in 10 patients. One patient had multi-resistant TB. PR of TBM developed in 5 patients despite concomitant corticosteroids in 4. Two cases had refractory PR. Case 1. 22 year old Vietnamese male presented with 6 week history of progressive headache and neck stiffness. CSF demonstrated 61 WCC (75% neutrophils), protein 2.67 g/L (n<0.45), glucose 2.1 mmol/L. Despite concomitant anti-tuberculosis and high-dose corticosteroid treatment, he developed worsening headaches and altered mentation with interval MRI brain increase in size and number of tuberculomas, hydrocephalus, and left thalamic infarction. Cyclosporin was added with gradual improvement and ultimately good outcome. Case 2. 47 year old Filipino male presented with 3 week history of headache and neck stiffness and 3 day history of fever, dysarthria and diplopia. MRI brain showed basal meningitis, hydrocephalus and left putaminal infarction. CSF demonstrated 245 WCC (35% neutrophils), protein 0.68 g/L, glucose 1.8 mmol/L. Despite concomitant anti-tuberculosis and corticosteroid treatment, the patient developed PR-induced worsening hydrocephalus necessitating ventriculo-peritoneal shunting. Cyclosporin was added with gradual PR resolution. Conclusion: Our case series highlights the importance of concomitant corticosteroids in TBM and the potential role of cyclosporin in refractory PR.